2005
DOI: 10.1016/j.bbamem.2005.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and in vivo evaluation of PEGylated spherulite formulations

Abstract: Spherulites are multilamellar vesicles obtained by shearing a lamellar phase of lipids and surfactants. They consist of concentric bilayers of amphiphiles alternating with layers of aqueous medium in which hydrophilic drugs can be sequestered with high yield. To be useful for drug targeting applications, spherulites should be small and long circulating. The objectives of this work were threefold. First, the spherulite size was optimized to obtain a mean diameter of less than 300 nm. Second, the vesicle composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…TW80-containing spherulites (formulation 1–3 ) had substantially smaller sizes (170–200 nm in diameter), suggesting that the structure of surfactants has a significant effect in controlling the sizes of the spherulites. This is consistent with the study by Simard et al, in which they showed that Tween 20 and 80 provided spherulites with smaller sizes than another surfactant, Solutol HS 15 (25). The underlying mechanism for the reduced size of TW80 formulations is likely due to its relatively high HLB value and small packing parameter based on its relatively large hydrophilic head group.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…TW80-containing spherulites (formulation 1–3 ) had substantially smaller sizes (170–200 nm in diameter), suggesting that the structure of surfactants has a significant effect in controlling the sizes of the spherulites. This is consistent with the study by Simard et al, in which they showed that Tween 20 and 80 provided spherulites with smaller sizes than another surfactant, Solutol HS 15 (25). The underlying mechanism for the reduced size of TW80 formulations is likely due to its relatively high HLB value and small packing parameter based on its relatively large hydrophilic head group.…”
Section: Resultssupporting
confidence: 93%
“…We also did not quantitatively measure the amounts of PEG conjugates incorporated into the spherulites considering the high efficiency of postinsertion approach with both unilamellar liposomes and spherulites (23, 25). More studies are needed in the future to define the optimal amounts of PEG-lipid and ligand-derivatized PEG-lipid for in vivo drug delivery.…”
Section: Resultsmentioning
confidence: 99%
“…After administration, spherulites should exhibit long in vivo circulation times to maximize their detoxification efficiency in the body. This could be easily achieved by incorporating poly(ethylene glycol) lipid derivatives in the vesicle membrane [24]. Future studies in live animal models should provide a comprehension of the relationship between in vivo circulation of the formulation and drug transfer kinetics to the prompt alleviation of drug-induced toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Up to now, many studies have highlighted that the physicochemical characteristics of nanoparticles are influenced by PEG molecule's weight (Simard et al 2005). However, details on the effect of PEG molar ratio have never been discussed, let alone investigating the potential mechanism.…”
Section: Introductionmentioning
confidence: 97%